Co-ACT—a framework for observing coordination behaviour in acute care teams. Issue 7 (19th March 2013) - Kolbe, Michaela; Burtscher, Michael Josef; Manser, Tanja
Abstract : Background: Acute care teams (ACTs) represent action teams, that is, teams in which members with specialised roles must coordinate their actions during intense situations, often under high time pressure and with unstable team membership. Using behaviour observation, patient safety research has been focusing on defining teamwork behaviours—particularly coordination—that are critical for patient safety during these intense situations. As one result of this divergent research landscape, the number, scope and variety of applied behaviour observation taxonomies are growing, making comparison and convergent integration of research findings difficult. Aim: To facilitate future ACT research by presenting a framework that provides a shared language of teamwork behaviours, allows for comparing previous and future ACT research and offers a measurement tool for ACT observation. Method: Based on teamwork theory and empirical evidence, we developed Co-ACT—the Framework for Observing Coordination Behaviour in ACT. Integrating two previous, extensive taxonomies into Co-ACT, we also suggested 12 behavioural codes for which we determined inter-rater reliability by analysing the teamwork of videotaped anaesthesia teams in the clinical setting. Results: The Co-ACT framework consists of four quadrants organised along two dimensions (explicit vs implicit coordination; action vs information coordination). Each quadrant provides three categories for which Cohen's κ overall value was substantial; but values for single categories varied considerably. Conclusions: Co-ACT provides a framework for organising behaviour codes and offers respective categories for succinctly measuring teamwork in ACTs. Furthermore, it has the potential to allow for guiding and comparing ACTs study results. Future work using Co-ACT in different research and training settings will show how well it can generally be applied across ACTs.